Strategies in Managing Human Resource Development in the 21st Century Education Era: A Case Study of Platinum Qur'an Kindergarten - Mumtazah, Durrotun; Darsinah; Rohmah, Wafrotur (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
The current era of development demands continuous improvement in the knowledge and skills of human resources. The effective management of teacher development in the field of education requires well-structured approaches. This study aims to describe and explain human resource development management in the context of 21st-century education at Qur'an Platinum Kindergarten, covering the planning, implementation, and evaluation stages. A qualitative research method was employed, using a descriptive case study approach. Data collection techniques involved observation, interviews, and documentation, while data analysis utilized technical and source triangulation. The findings indicate that human resource development management in the 21st-century education era begins with planning, employing techniques such as SWOT analysis and open discussions. The implementation phase utilizes the off-the-job training method model. Training and development activities incorporate various models, including lecture-based instruction, student-centered approaches, project-based learning, collaborative learning, simulation learning, discovery learning, and flipped classroom strategies. The evaluation of outcomes takes place every month without conducting tests. We perform technical assessments at the end of the school year, while follow-up actions are carried out through normal processes